(untitled) (Medicine Today, 2026)
Introduction: Cervical cancer is the second most common cancer in female with high morbidity and mortality. Worldwide, cervical cancer is the fourth most occurring malignancy and results in an estimated 530,000 new cases annually with 270,000 deaths. In many developed countries, health education, awareness programs and early detection and appropriate management achieve 80% reduction in mortality. Cervical cancer death is successfully prevented in developed countries by cervical cytology screening. Methods: This was a comparative cross sectional study conducted in Gynaecological Oncology Department of Bangabandhu Sheikh Mujib Medical University. Duration of the study was one year from July 2018 to June 2019. It was aimed to evaluate the performance status of Pap’s smear as a screening test for cervical cancer. Sample size was Hundred and Pap’s smear were collected at GOPD. Cytology of the sample were done by conventional method. All the patients underwent colposcopy and directed biopsy at the colposcopy clinic of Gynae Oncology. Result: The result shows maximum (44%) patients had first intercourse at 10-15 years of age. Maximum (72%) patients came from low socioeconomic condition. The specificity and positive predictive value of pap’s test was found as 81% and 52.63% respectively. According to pap’s report 19% patients were positive and according to colposcopy biopsy 59% patients were positive for cervical intraepithelial neoplasia. Conclusion: Cervical cancer screening for the early diagnosis of CIN, pap’s smear is mandatory. VIA as a screenings test is not sufficient for the postmenopausal women. Medicine Today 2026, Vol.38 (1): 129-132